Cobaloximes: selective nitrite reduction catalysts for tandem ammonia synthesis. Issue 4 (1st March 2023) - Meng, Shu-Lin; Zhang, Chen; Ye, Chen; Li, Jia-Hao; Zhou, Shuai; Zhu, Lei; Li, Xu-Bing; Tung, Chen-Ho; Wu, Li-Zhu
Abstract : Herein, we demonstrate cobaloximes as a bioinspired molecular platform for exclusive ammonia synthesis via electrocatalytic NO2 − reduction (eNO2 − RR), which attained 98.5% faradaic efficiency (FE) under close-to-neutral conditions. Abstract : Herein, we demonstrate cobaloximes as a bioinspired molecular platform for exclusive ammonia synthesis via electrocatalytic NO2 − reduction (eNO2 − RR), which attained 98.5% faradaic efficiency (FE) under close-to-neutral conditions. Mechanistic studies illustrated that cobaloximes furnished effective binding with NO2 − and nitrogenous intermediates, along with continuous, rapid 6e − /8H + transfer with an intramolecular hydrogen bonding framework. As the cobaloxime skeleton displayed tunable structures on axial and equatorial sites for selective NO2 − to NH4 + transformation, integrating cobaloximes with multi-walled carbon nanotubes (MWCNTs) as working electrodes attained advantageous ammonia yields of 19.3 mg h −1 mgCat −1 with >95% FE at −0.5 V vs. RHE. More strikingly, cobaloxime-catalyzed NO2 − to NH4 + transformation was coupled with plasma-driven N2 oxidation (pNOR) to convert ambient air into NH4 Cl at a mmol-scale. This work demonstrates promising prospects of bioinspired molecular catalytic platforms for effective and selective ammonia and nitrogenous chemical synthesis via NO x − .